ECONOMIC AND FINANCIAL FEASIBILITY OF PORT DEVELOPMENT IN EAST KALIMANTAN PROVINCE - Theresita Herni Setiawan; Finnegan Belano; Adrian Firdaus; Andreas Franskie Van Roy; Yohanes Lim Dwi Adianto; Aloysius Tjia Iwan Irawan (Jurnal Transportasi, 2022)
Abstract The port is an infrastructure that connects land and sea transportation modes, which greatly affects the movement of goods and passengers. The construction or development of a port requires an in-depth study, because it is associated with large costs. Several parameters are needed to conduct a feasibility study for the construction of a port, which includes the demand for loading and unloading of goods and ship visits. In this study, a feasibility study was conducted on the construction of a port in East Kalimantan Province. This study shows that the planned development of a port in East Kalimantan Province is economically feasible but not financially viable. Keywords: port; development feasibility; economic feasibility; financial feasibility. Abstrak Pelabuhan merupakan infrastruktur yang menghubungkan moda transportasi darat dan moda transportasi laut, yang sangat berpengaruh terhadap pergerakan barang dan penumpang. Pembangunan atau pengembangan suatu pelabuhan memerlukan kajian yang mendalam, karena terkait dengan biaya yang besar. Diperlukan beberapa parameter untuk melakukan kajian kelayakan pembangunan suatu pelabuhan, yang mencakup kebutuhan bongkar muat barang dan kunjungan kapal. Pada studi ini dilakukan kajian kelayakan pembangunan suatu pelabuhan di Provinsi Kalimantan Timur. Studi ini menunjukkan bahwa rencana pembangunan suatu pelabuhan di Provinsi Kalimantan Timur layak secara ekonomi tetapi tidak layak secara finansial. Kata-kata kunci: pelabuhan; kelayakan pembangunan; kelayakan ekonomi; kelayakan finansial.